OLDER GENERATION ROLE IN THE PRESERVATION OF TRADITIONAL FAMILY VALUES (ON THE REPUBLIC EXAMPLE NORTHERN OSSETIA-ALANIA) - V. Tarchenko (Вестник университета)
The article is devoted to the study of family values of pensioners of the Republic of North Ossetia-Alania. The study found that the family is the main value of the older generation. The family serves as a source of values and guide of traditions, and imposes on family members certain duties and responsibilities.